0150 Bake Your Own Ophthalmic Laser Course. (1st November 2014) - Dickerson, Polly; Innes, James; Arora, Seema; Elsherbiny, Samer; Hamilton, Robin; Oxley, Lucy
Abstract : Background: The Royal College of Ophthalmologists (RCOphth) recently introduced a laser technical skills simulation course to their Annual Congress, consistent with training curriculum requirements (RCOphth 2014). Developed by consultants with expertise in laser training, it is aimed at junior trainees and designed to simulate retinal, posterior capsule, iris and angle laser treatments. While the course developers already run local laser simulation teaching, in some regions laser training is ad hoc. We describe the process and requirements for setting up a structured simulated laser course to create a "recipe book". This should allow trainers to set up comparable courses regionally, democratising access to simulation-based training in ophthalmic laser treatments. Methods: The recipe book contains the information needed to run a simulated technical skills course for ophthalmic laser, including: pre-course knowledge requirements for candidates, including laser safety; equipment requirements; environmental considerations to ensure laser safety; faculty requirements; instructions to candidates; debriefing suggestions; advice on incorporating assessment. Results: The recipe book will enable all training regions to provide an equivalent standard of laser simulation training to their ophthalmology trainees. We would expect wider access to technical simulation to translate to higher standards in laser service provision, and therefore improvement in patient care. The authors aim to gain RCOphth accreditation for the recipe book. Potential impacts: Due to increasing valuation of simulation in surgical training, we expect that formal laser simulation training will become mandatory in UK ophthalmic specialist training. Combined with RCOphth accreditation, this may drive use of the recipe book. We believe that improved technical skills training via the proven methodology of simulation (Cook et all 2011) will improve the quality of laser treatment given to patients, which should improve patient safety. This hypothesis forms the basis for future work by the course development group. References: RCOphth (2014) Curriculum for Ophthalmic Specialist Training RCOphth, London http://curriculum.rcophth.ac.uk/study-guide/surgical_skills Cook DA, Hatala R, Brydges R, et al . Technology-enhanced simulation for health professions education. JAMA 2011;306:978–88